Integrasi Teknologi dalam Upaya Penegakan Hukum di Indonesia: Perspektif Hukum dan Regulasi - Briliant Pangabean, Bona Axel; Kemala, Anyelir Puspa (Neolectura, 2025)
The development of technology in the legal system in Indonesia has brought significant changes to the judicial process. Digitalization of law through the implementation of e-Court, artificial intelligence (AI), big data, and blockchain provides great opportunities to increase efficiency, accessibility, and transparency in law enforcement. Various regulations have been drafted to support the integration of technology in the judicial system, including Law No. 11 of 2008 concerning Electronic Information and Transactions (UU ITE), Law No. 27 of 2022 concerning Personal Data Protection, and Supreme Court Regulation No. 3 of 2018 concerning e-Court. However, the implementation of this technology also raises various challenges, such as the validity of digital evidence, protection of privacy rights, and the readiness of legal infrastructure and human resources. This study uses normative legal methods with a statutory, conceptual, jurisprudential, and comparative approach to evaluate how the legal system in Indonesia adapts to technological developments in law enforcement. The results of the study show that although regulations related to legal technology have been implemented, there are still weaknesses in the mechanisms for protecting human rights, authenticating digital evidence, and protecting data in the legal process. In addition, a comparison with regulations in the European Union and the United Kingdom shows that the legal system in Indonesia needs to improve the standards for validating electronic evidence and protecting personal data. Therefore, a more comprehensive legal reform is needed to ensure that the use of technology in the legal system remains in line with the principles of justice and legal certainty. By strengthening regulations, increasing the capacity of law enforcement officers, and synergy between the government, academics, and legal practitioners, the Indonesian legal system can develop adaptively and continue to uphold the principles of justice in the digital era